Complementary autophagy inhibition and glucose metabolism with rattle-structured polydopamine@mesoporous silica nanoparticles for augmented low-temperature photothermal therapy and in vivo photoacoustic imaging - Shao, Leihou (Theranostics, 2020)
Rattle-structured nanoparticles with movable cores, porous shells and hollow interiors have shown great effectiveness in drug delivery and cancer theranostics. Targeting autophagy and glucose have provided alternative strategies for cancer intervention therapy. Herein, rattle-structured polydopamine@mesoporous silica nanoparticles were prepared for in vivo photoacoustic (PA) imaging and augmented low-temperature photothermal therapy (PTT) via complementary autophagy inhibition and glucose metabolism. Methods: The multifunctional rattle-structured nanoparticles were designed with the nanocore of PDA and the nanoshell of hollow mesoporous silica (PDA@hm) via a four-step process. PDA@hm was then loaded with autophagy inhibitor chloroquine (CQ) and conjugated with glucose consumer glucose oxidase (GOx) (PDA@hm@CQ@GOx), forming a corona-like structure nanoparticle. Results: The CQ and GOx were loaded into the cavity and decorated onto the surface of PDA@hm, respectively. The GOx-mediated tumor starvation strategy would directly suppress the expression of HSP70 and HSP90, resulting in an enhanced low-temperature PTT induced by PDA nanocore. In addition, autophagy inhibition by the released CQ made up for the loss of low-temperature PTT and starvation efficiencies by PTT- and starvation-activated autophagy, realizing augmented therapy efficacy. Furthermore, the PDA nanocore in the PDA@hm@CQ@GOx could be also used for PA imaging. Conclusion: Such a “drugs” loaded rattle-structured nanoparticle could be used for augmented low-temperature PTT through complementarily regulating glucose metabolism and inhibiting autophagy and in vivo photoacoustic imaging.